Chemistry for today - Seager, Spencer L.
You will quickly gain a comprehensive understanding of chemistry with this new Sixth Edition of CHEMISTRY FOR TODAY: GENERAL, ORGANIC, AND BIOCHEMISTRY. Using real-life applications and interactive technology tools, this text will show you how chemistry relates to health science. The thorough integration of online assessment and learning tools turns study time into experiences with chemistry--helping you gain true comprehension of chemical concepts. CHEMISTRY FOR TODAY will help dispel any fear you may have of chemistry as it helps you appreciate the role chemistry plays in our daily lives through a rich pedagogical structure and an accessible writing style with lucid explanations. In addition, Seager and Slabaugh's CHEMISTRY FOR TODAY provides greater support in both the problem-solving and critical-thinking skills needed to succeed in chemistry. By illustrating how this information will help your future career and providing important career information online, the authors help you set goals and focus on achieving them